Finite Element Analysis of the Box of a New-type of Planetary Reducer with Few Teeth Difference - Zhai Cong; Yang Shuncheng; Xiao Xin (Jixie chuandong)
The structure of the new-type of the planetary reducer with few teeth difference,which is proposed by Xiao Nanping and received the patent for this invention are introduced. The finite element model of this reducer box is established by using the software ANSYS Workbench. The statics analysis is carried out,the changing curve for each actual loading conditions of the reducer box,and the changing curve of the maximum stress and the deformation are obtained,this analysis results can provide the data support for the subsequent structure improvement and weight reduction. The natural frequency and vibration type are obtained by completing the modal analysis of this box,and whether the resonance phenomenon happens can be determined by comparing the natural frequency of this reducer with the meshing frequency and the rotational frequency. It also offers a theoretic reference for the structure optimization design and following research of vibration problems for reducers.